PELESAPAN SUBJEK DAN PREDIKAT PADA JUDUL-JUDUL BERITA LINE NEWS POPULER - Faraba, Karina Sofiananda Armaza (Universitas Negeri Surabaya, 2017)
The research problems are to be examined are (1) how the deletion subject and predicate in the headlines Line News Popular? (2) why the subject and predicate in the headlines Line Popular News dilesapkan? The data used is the news in the media Line Today. Application Line is a popular social media are widely used community understand the progress of technology. Inside Line application that there is a collection that can read the latest news. The method used by researchers is a descriptive analytical research methods. The data collection was done by using refer to the note. Results of the 10 data amalisis popular news headlines found in Line News Popular on December 4, 2016 at 6 clause found in the headline that experienced an ellipsis or deletion. Precisely, 4 clause experiencing fading Subject (S) and the second clause experiencing fading Predicate (P) and S + P.